2017
DOI: 10.1259/bjr.20170216
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT vs CT-scan in patients with pulmonary metastases previously operated on for colorectal liver metastases

Abstract: Although CT-scans have a greater capacity to detect PMCRC, the F-FDG PET/CT could be useful in the detection of more pulmonary and extrapulmonary disease not identified by the CT-scan. Advances in knowledge: We tried to clarify the utility ofF-FDG PET/CT in the management of this subpopulation of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Imaging is not only used for diagnosis and follow-up of lung metastases but can also support and guide local treatment such as thermal treatments (generally CT-guided), namely radiofrequency, microwave, cryotherapy [11]. Nuclear medicine, especially with radiologic imaging fusion—positron emission tomography-computed tomography (PET-CT) and positron emission tomography-magnetic resonance imaging (PET-MRI), allows the coupling of morphologic data from imaging with physiological data on the uptake of radiotracers [12].…”
Section: Clinical and Radiological Presentation Of Pulmonary Metasmentioning
confidence: 99%
“…Imaging is not only used for diagnosis and follow-up of lung metastases but can also support and guide local treatment such as thermal treatments (generally CT-guided), namely radiofrequency, microwave, cryotherapy [11]. Nuclear medicine, especially with radiologic imaging fusion—positron emission tomography-computed tomography (PET-CT) and positron emission tomography-magnetic resonance imaging (PET-MRI), allows the coupling of morphologic data from imaging with physiological data on the uptake of radiotracers [12].…”
Section: Clinical and Radiological Presentation Of Pulmonary Metasmentioning
confidence: 99%
“…In the present study, an increase in the use of ceMRI in the Netherlands was observed, whereas use of 18F-FDG PET-CT decreased. These trends are probably the result of international publications 4,7,8,10,12,13,15,31,34 reporting the additional value of these imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Detection rates are lower in patients who have received preoperative chemotherapy. One RCT investigated the additional value of 18 F‐FDG PET–CT in CRLM and concluded that this did not influence survival, whereas several unrandomized studies indicated that there could be added value for 18 F‐FDG PET–CT in patients with extrahepatic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…18 F fluorodeoxyglucose PET/computed tomography ( 18 F-FDG PET/CT) imaging provides semiquantitative analysis of glucose uptake by lesions, and the degree of FDG uptake in lesions is often expressed as the standardized uptake value (SUV), with the maximum standardized uptake value (SUV max ) being the most commonly used metabolic parameter to assess tumor metastasis, determine staging and guide treatment. Compared to normal CT scans, the specificity of 18 F-FDG PET/CT for the diagnosis of CRLM is increased by 19%, and 18 F-FDG PET/CT can detect more CRLM lesions [8,9].…”
Section: Introductionmentioning
confidence: 99%